The impact of particles on the collapse characteristics of cavitation bubbles. (1st February 2017) - Xu, Weilin; Zhang, Yalei; Luo, Jing; Arong,; Zhang, Qi; Zhai, Yanwei
Abstract: Water-sand two-phase flows often pass through the water passages of hydraulic and hydropower projects. Aided by high-speed photography, the impact on the collapse characteristics of the cavitation bubbles of particles was researched at the mesoscopic level in this paper. The experiments yielded the following results. (1) Particles impact the form and direction of collapse of cavitation bubbles. The significance of the impact increases as the particle size increases. (2) The impact of the dimensionless distance and size ratio between the particle and the cavitation bubble on the direction of collapse of the cavitation bubble has a quantitative relationship. (3) The impact of the dimensionless distances between the particle and the wall and the cavitation bubble on the direction of collapse can be divided into five regions. Particles alleviate cavitation and protect the wall by changing the direction of collapse of the cavitation bubble under some conditions. These conclusions are theoretically important for controlling cavitation damage in water-sand two-phase flows. Highlights: The impact on the collapse characteristics of the cavitation bubble of particles was studied at the meso-level. The impact of the dimensionless distance and size ratio between the particle and the cavitation bubble on the direction of collapse of the cavitation bubble can be quantitatively related. A particle alleviates cavitation erosion on the wall by changing the direction of the collapse of the cavitation bubble or by absorbing it.